Microstructural characterization of spray-dried NiO-8YSZ particles as plasma sprayable anode materials for metal-supported solid oxide fuel cell. Issue 10 (July 2017) - Hwang, Inhwan; Jeong, Jongku; Lim, Kyoungtae; Jung, Jinmu
Abstract: The plasma spray method is widely used to produce NiO-8YSZ (composed of nickel oxide (NiO) and 8 mol% yttria-stabilized zirconia) anode layers in metal-supported solid oxide fuel cell (SOFC). Flowability control of microsized particles is important for achieving consistent performance of the SOFC anode layer. When microsized particles are fabricated via spray drying and sintering, the most significant factors that influence flowability are their sizes, distribution, and surface conditions. Thus, the aim of this study is to analyze the fabrication conditions for microsized NiO-8YSZ cermet particles made from a nanoscale, sinterable NiO-8YSZ dispersion solution by using an appropriate spray-drying and sintering process. The characteristics of the as-sprayed and sintered NiO-8YSZ composite particles (such as size, distribution, roughness, and nanostructure) were analyzed via field emission scanning electron microscope (FE-SEM), energy dispersive spectroscopy (EDS), particle size distribution (PSD), Brunauer–Emmett–Teller (BET) surface area, and atomic force microscopy (AFM). The as-sprayed microsized NiO-8YSZ particles became smaller and more uniformly distributed as the rotational speed used for spray drying increased. As a result of sintering, the extent of shrinkage of as-sprayed microsized NiO-8YSZ particles generated at high RPMs was lower than that of particles formed at low RPMs. No significant difference was observed in the distribution of the nanosized NiO and 8YSZ particles at different rotational speeds. Furthermore, the highest BET surface areas were observed for particles generated at 8000 RPM before sintering at 13.74 m 2 /g. After sintering, the highest BET surface area was 0.94 m 2 /g for particles generated at 16, 000 RPM. Differences in nanostructure and surface roughness between as-sprayed and sintered microsized NiO-8YSZ particles were identified via AFM. This study is expected to provide important fundamental information useful for optimizing SOFC efficiency by promoting flowability control during the production of SOFC anodes via plasma spraying.